Gene expression profiling in healthy newborns from diverse localities of the Czech Republic - Honkova, Katerina; Rossnerova, Andrea; Pavlikova, Jitka; Svecova, Vlasta; Klema, Jiri; Topinka, Jan; Milcova, Alena; Libalova, Helena; Choi, Hyunok; Veleminsky, Milos; Sram, Radim J; Rossner, Pavel (Environmental and molecular mutagenesis, 2018)
Prenatal exposure to air pollution is associated with intrauterine growth restriction and low birth weight. Gene expression changes in newborns in relation to air pollution have not been sufficiently studied. We analyzed whole genome expression in cord blood leukocytes of 202 newborns from diverse localities of the Czech Republic, differing among other factors in levels of air pollution: the district of Karvina (characterized by higher concentration of air pollutants) and Ceske Budejovice (lower air pollution levels). We aimed to identify differentially expressed genes (DEGs) and pathways in relation to locality and concentration of air pollutants. We applied the linear model to identify the specific DEGs and the correlation analysis, to investigate the relationship between the concentrations of air pollutants and gene expression data. An analysis of biochemical pathways and gene set enrichment was also performed. In general, we observed modest changes of gene expression, mostly attributed to the effect of the locality. The highest number of DEGs was found in samples from the district of Karvina. A pathway analysis revealed a deregulation of processes associated with cell growth, apoptosis or cellular homeostasis, immune response-related processes or oxidative stress response. The association between concentrations of air pollutants and gene expression changes was weak, particularly for samples collected in Karvina. In summary, as we did not find a direct effect of exposure to air pollutants, we assume that the general differences in the environment, rather than actual concentrations of individual pollutants, represent a key factor affecting gene expression changes at delivery. Environ. Mol. Mutagen. 59:401-415, 2018. © 2018 Wiley Periodicals, Inc.
Keywords: polycyklické aromatické uhlovodíky; novorozenec; Infant, Newborn; Pregnancy; Humans; regulace genové exprese; PM2.5; Environmental Monitoring; Female; cord blood; vystavení vlivu životního prostředí; lidé; Air Pollution; Air Pollutants; Polycyclic Aromatic Hydrocarbons; microarray; Fetal Blood; látky znečišťující vzduch; monitorování životního prostředí; ženské pohlaví; Gene Expression Regulation; fetální krev; air pollution; stanovení celkové genové exprese; těhotenství; Czech Republic; Environmental Exposure; benzo[a]pyrene; prenatal exposure; znečištění ovzduší; Gene Expression Profiling; Česká republika